Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan di Provinsi Papua dan Papua Barat - Salim, Agus; Khoirudin, Rifki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze what factors can reduce poverty rates in Papua and West Papua Provinces. This study uses secondary data with a quantitative approach. The analysis tool used is STATA 14. The type of data used in this study is panel data consisting of 29 districts/cities in Papua Province in the period 2010-2021. The research data comes from the official website of the Papua Province Central Statistics Agency and the Annual Report of the Indonesian Ministry of Finance. The results of the study show that government spending and unemployment have a positive and significant effect on poverty in districts/cities in Papua and West Papua.